A cohort study of the association between maternal serum Inhibin-A and adverse pregnancy outcomes: a population-based study - Wannaporn Singnoi; Chanane Wanapirak; Ratanaporn Sekararithi; Theera Tongsong (BMC, 2019)
Abstract Background To compare the rates of adverse pregnancy outcomes between women with normal and abnormal inhibin-A levels. Methods Based on a prospective database of Down syndrome screening program, the consecutive records were comprehensively reviewed. Pregnancies were classified into three groups: normal, high (> 2 MoM) and low (< 0.5 MoM) inhibin-A levels. The pregnancies with medical diseases, chromosome abnormalities and fetal anomalies were excluded. The primary outcomes were the rates of preterm birth, preeclampsia, and fetal growth restriction (FGR). Results Of 6679 recruited pregnancies, 5080 met the inclusion criteria, including 4600, 205 and 275 pregnancies in the group of normal, high, and low inhibin-A levels respectively. The rates of preterm birth, preeclampsia and FGR were significantly higher in the group of high levels; (RR, 1.51, 95%CI: 1.01-2.26; 3.47, 95% CI: 2.13-5.65; 3.04, 95% CI: 1.99-4.65 respectively), whereas the rates of other adverse outcomes were comparable. However, the rate of spontaneous preterm birth among women with high inhibin-A was not significantly increased. Based on multivariate analysis, the preterm birth rate was not significantly associated with inhibin-A levels, but it was rather a consequence of preeclampsia and FGR. Low levels of serum inhibin-A were not significantly associated with any adverse outcomes. Conclusions High levels of maternal serum inhibin-A in the second trimester are significantly associated with abnormal placentation, which increases the risk of preeclampsia and FGR with a consequence of indicated preterm birth but not a risk of spontaneous preterm birth. In contrast, low inhibin-A levels were not associated with any common adverse pregnancy outcomes.